Collaborative Learning in Expeditions to Knowledge (2011)
In 2011, children and young people participating in Expeditions to Knowledge formed teams to develop research projects related to their own questions. But what does it really mean to work as a team?, how to achieve it?, what role do mentors play in this kind of work? Although Expeditions to Knowledge is not a formal collaborative learning practice, we share a constructivist position of teaching and learning.